Mapping the Effect of Cupping Therapy on Body Health: A Bibliometric Analysis - Achmad Budi Santoso; MG Catur Yuantari; Supriyono Asfawi (Universitas Pahlawan Tuanku Tambusai, 2025)
Cupping therapy is a traditional treatment method that has been used for centuries. This study aims to map the effects of cupping therapy on body health based on existing literature. This study reviews various scientific articles that discuss physiological effects, mechanisms of action, and benefits and potential risks. The review results show that cupping therapy has a positive effect on improving blood circulation, relieving pain, and reducing inflammation. However, further research is needed to strengthen the scientific evidence supporting the application of this therapy in modern medical practice.